Partial replacement of corn by soybean hulls in high-grain diets for feedlot sheep - Homem Junior, Antonio Carlos [UNESP]; Nocerao, Bruno Faleiros [UNESP]; Faleiros, Lucas Figueiredo [UNESP]; Costa Almeidao, Marco Tulio [UNESP]; Paschoaloto, Josimari Regina [UNESP]; Perez, Henrique Leal [UNESP]; D'Aurea, Andre Pastori [UNESP]; Bertocco Ezequiel, Jane Maria [UNESP] (Empresa Brasil Pesq Agropec, 2019)
The objective of this work was to evaluate the partial replacement of corn grains by soybean hulls, in high-grain diets, and its effect on the feeding behavior and ruminal fermentation parameters of feedlot sheep. Eight rumen-cannulated crossbred sheep were assigned to four treatment groups composed of a control, to fed a diet of 50% corn silage and 50% concentrate, and to three groups fed high-grain diets, as follows: 85% corn (Diet85), 75% corn plus 10% soybean hulls (Dict75), and 65% corn plus 20% soybean hulls (Diet65). High-grain diets reduced rumination time and provided a higher degradation of feed dry matter, a higher-propionic acid concentration, a loweracetic acid concentration, a lower methane and carbon dioxide gas production, and a lower ruminal pH value. Diet65. with 20% soybean hulls, promoted an increase in the acetic acid proportion, with a reduction in the CO2:CH4 ratio. At the end of in vitro incubation, the pH value was higher for the control diet, and it was lower for Diet85. The inclusion of soybean hulls does not change methane production and dry matter degradation, and it can be used to substitute up to 20% of corn grain in high-grain diets.
Keywords: carbon dioxide; dry matter degradation; ingestive behavior; methane gas; short-chain fatty acids